New taxonomical combinations in some genera of Bacillariophyta - Bukhtiyarova, L.N.; Compere, P. (Альгология, 2006)
В результаті інвентаризації флори діатомових водоростей України запропоновано 7 нових таксономічних комбінацій. Серед них 4 – для роду Ulnaria (Kutz.) Compere та 3 – для родів Neosynedra Williams et Round, Astartiella Witkowki, Lange-Bertalot et Metzeltin та Lemnicola Round et Basson. Seven new taxonomical combinations are proposed, four combinations – for the genus Ulnaria (Kutz.) Compere and three other ones – for Neosynedra Williams et Round, Astartiella Witkowki, Lange-Bertalot et Metzeltin and Lemnicola Round et Basson because of Ukrainian diatom flora arrangement.